Adherence to the antirheumatic drugs: a systematic review and meta-analysis - Aksoy, Nilay; Ozturk, Nur; Agh, Tamas; Kardas, Przemyslaw (Frontiers in Medicine, 2024)
Introduction This systematic review and meta-analysis aimed to analyze the adherence rate for conventional and biological disease-modifying antirheumatic drugs (DMARDs) utilizing different assessment measures. Method A systematic literature search was performed in four electronic databases, including PubMed, Scopus, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL), covering the time frame from April 1970 to April 2023. Studies that present data on medication adherence among adult patients with rheumatoid arthritis (RA), specifically focusing on DMARDs (conventional or biological), were included in the analysis. The adherence rate for different assessment measures was documented and compared, as well as for conventional and biological DMARDs. A random-effects meta-analysis was performed to assess adherence rates across different adherence assessment measures and drug groups. Results The search identified 8,480 studies, out of which 66 were finally included in the analysis. The studies included in this meta-analysis had adherence rates ranging from 12 to 98.6%. Adherence rates varied across several adherent measures and calculation methods. Using the subjective assessment measures yielded the outcomes in terms of adherence rate: 64.0% [0.524, 95% CI 0.374–0.675] for interviews and 60.0% [0.611, 95% CI 0.465–0.758] for self-reported measures (e.g., compliance questionnaires on rheumatology CQR-5), p > 0.05. In contrast, the objective measurements indicated a lower adherence rate of 54.4% when using the medication event monitoring system (p > 0.05). The recorded rate of adherence to biological DMARDs was 45.3% [0.573, 95% CI 0.516–0.631], whereas the adherence rate for conventional DMARDs was 51.5% [0.632, 95% CI 0.537–0.727], p > 0.05. In the meta-regression analysis, the covariate “Country of origin” shows a statistically significant (p = 0.003) negative effect with a point estimate of −0.36, SE (0.12), 95% CI, −0.61 to −0.12. Discussion Despite its seemingly insignificant factors that affect the adherence rate, this meta-analysis reveals variation in adherence rate within the types of studies conducted, the methodology used to measure adherence, and for different antirheumatic drugs. Further research is needed to validate the findings of this meta-analysis before applying them to clinical practice and scientific research. In order to secure high reliability of adherence studies, compliance with available reporting guidelines for medication adherence research is more than advisable.